Dynamics of Centrosome Translocation and Microtubule Organization in Neocortical Neurons during Distinct Modes of Polarization. (10th January 2013) - Sakakibara, Akira; Sato, Toshiyuki; Ando, Ryota; Noguchi, Namiko; Masaoka, Makoto; Miyata, Takaki
Abstract : Neuronal migration and process formation require cytoskeletal organization and remodeling. Recent studies suggest that centrosome translocation is involved in initial axon outgrowth, while the role of centrosomal positioning is not clear. Here, we examine relations between centrosomal positioning, axonogenesis, and microtubule (MT) polarization in multipolar and bipolar neocortical neurons. We monitored dynamic movements of centrosomes and MT plus ends in migratory neurons in embryonic mouse cerebral slices. In locomoting bipolar neurons, the centrosome oriented toward the pia-directed leading process. Bipolar neurons displayed dense MT plus end dynamics in leading processes, while trailing processes showed clear bidirectional MTs. In migrating multipolar neurons, new processes emerged irrespective of centrosome localization, followed by centrosome reorientations toward the dominant process. Anterograde movements of MT plus ends occurred in growing processes and retrograde movements were observed after retraction of the distal tip. In multipolar neurons, axon formed by tangential extension of a dominant process and the centrosome oriented toward the growing axon, while in locomoting neurons, an axon formed opposite to the direction of migration and the centrosome localized to the base of the leading process. Our data suggest that MT organization may alter centrosomal localization and that centrosomal positioning does not necessarily direct process formation.